LANGUAGE LEARNING STRATEGIES IN ENGLISH AS A FOREIGN LANGUAGE CLASSROOM IN INDONESIAN HIGHER EDUCATION CONTEXT - Tanjung, Firima Zona (LLT Journal: A Journal on Language and Language Teaching, 2018)
Indonesian university students are not well-familiar with language learning strategies (LLS) as they are dependent on their lecturers. This condition also gets worse because the students still have low level of proficiency although they have already been learning English for multiple years. There have been many researches on students LLS related to the four language skills and gender but there is a high need of studying the students LLS regarding their age in the Indonesian higher education context. This research aimed at investigating students language learning strategies related to their ages and providing some steps to make teaching program more effective by considering students LLS and their age as well. This research utilized descriptive survey research design. The participants were 122 English Department students at one of public universities in Borneo Island, Indonesia. The instrument was SILL questionnaire. All the collected data were analyzed statistically. The findings show that students mostly used metacognitive (M=3.857), cognitive (M=3.707), and compensation strategies (M=3.563). The students different age led them to select and implement different strategies. Some steps to optimize students learning strategies are through inserting LLS instruction in the curriculum of teaching program, implementing certain models of strategy instruction, and developing lecturers awareness of designing instruction at which one of the methods that can be employed is eclective methods. Considering all findings, it can be concluded that although indirect strategies get higher means of preference from the participants but they do not only focus on using indirect strategies. They combine those with direct strategies. Further, to make students more successful on their learning, the institution including lecturers and the academic community should take part in the effort of teaching learning strategies. This provides future research area that emphasizes on designing LLS instruction regarding students age and level of their education.